Development and Validation of the Integrated Inquiry Blended Learning (IIBL) Model Supported by Smart Learning to Support 21st-Century Skills in Vocational Engineering Education: A Design-Based Research Study - Irma Yulia Basri; Muhammad Giatman; Dony Novaliendry; Erni Marlina binti Saari; Riki Mukhaiyar; Ika Parma Dewi (International Journal of Educational Narratives, 2026)
Background. The learning process in vocational engineering electronics still faces challenges such as low student literacy, limited face-to-face learning time, and the need for experiment-based instruction. Previous studies have generally examined inquiry-based learning, blended learning, and digital learning separately, with limited integration into a structured Smart Learning–supported instructional model. Smart Learning facilitates digital resources, online discussions, assignment management, and flexible blended learning activities. Purpose. This study aims to develop and validate the Integrated Inquiry Blended Learning (IIBL) model supported by Smart Learning in vocational engineering education. Method. A Design-Based Research approach was employed through iterative processes of analysis, design, development, implementation, and evaluation, including expert validation, practicality testing, and effectiveness testing. Validation instruments were analyzed using SEM-PLS to ensure construct validity, while practicality was measured through student and lecturer perception surveys. Effectiveness was evaluated across three implementation cycles through analyses of cognitive, psychomotor, affective, and 21st-century skills, supported by paired sample t-tests comparing pre- and post-test scores in control and experimental groups. Results. The IIBL model was construct-valid, with outer loadings above 0.70, AVE above 0.50, CR above 0.70, and HTMT below 0.90. Practicality evaluations by lecturers and students reached a very high category, while effectiveness testing showed significant improvements in students’ cognitive, psychomotor, affective, and 21st-century skills. Conclusion. The developed IIBL model provides a validated instructional framework integrating inquiry-based learning, blended learning, and Smart Learning support, contributing a structured IIBL syntax empirically validated through SEM-PLS and demonstrating potential to enhance students’ engagement, practical competencies, and 21st-century skills.